(untitled) (Annals of Medical Research, 2021)
Aim: A growing number of findings suggest that there is an important relationship between upper airway obstruction (UAO) and specific learning disorder (SLD). However, existing evidence is limited to very few studies. We, thus, aimed to explore chronic UAO conditions in children with specific learning disabilities.Materials and Methods: This study involved seventy-seven children aged 7 to 10 years with SLD and eighty-six healthy children matching in age and gender. Psychiatric disorders were diagnosed through the Diagnostic and Statistical Manual of Mental Disorders (DMS-5) Criteria. Porteus Maze Test and Kent-EGY test were used to assess the intelligence of the participants. The diagnoses of UAO were made by a physical examination, a detailed otorhinolaryngologic examination, the anamnesis and clinical history, anterior rhinoscopy, and flexible endoscopic nasopharyngoscopy according to the type of UAO.Results: The rates of having at least one pathology causing UAO and secondary sleep difficulties due to UAO were significantly higher in children with SLD compared to controls. The severity of SLD was significantly associated with the severity of UAO and the presence of secondary sleep difficulties, but not the presence of UAO. The verbal and total IQ scores were significantly affected by the presence and severity of UAO, while the presence of secondary sleep difficulties significantly impacted all IQ scores.Conclusion: Parents, teachers, otorhinolaryngologists, child psychiatrists, and pediatricians should be aware that the association between learning disorders and UAO. It also would be advisable to screen children with learning disorders in terms of UAO, and vice versa.